Put'-doroga ('Along the road') - V.V. Kolesov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the systemic correlation of four lexical constituents of the concept “road”: doroga (дорога 'road'), put' (путь 'way'), tropa (тропа 'track'), and stezya (стезя 'path'). Correlations between these constituents have been shown based on their opposites, contrasts, and discrepancies, which develop a complete system of the content-bearing forms of the concept, i.e., the constructs of its image, idea, symbol, and mental conceptum (original meaning). A mental paradigm is built out of four constituents – the initial foundation and etiological forms having causative relations – condition, real cause, and final cause, i.e., aim. The mental paradigm is based on the series of semantic constants (stable relations) singled out from the exemplary texts; they actualize the meaning of the concept in the subconsciousness of the considered authors. The permanent features, which form (figurative) notions along with the names, have been revealed. The revision with the help of Dahl's Explanatory Dictionary proves the discovered relations are actual: put' is the basic conceptum, tropa is its image, doroga is the notion, stezya is the symbol. The conceptual meaning of the word becomes a hyperonym of the literary language as a compound with the largest number of distinguishing features.